PENGALAMAN INTERAKSI TUNANETRA PENGGUNA APLIKASI ANDROID GO-JEK DAN GRAB - Desideria Ristiani; Banung Grahita; Achmad Syarief (Fakultas Seni Rupa dan Desain ITB, 2021)
This study on the interactional experience of people who have visual impairments or disabilities in using Go-jek and Grab Android applications employs usability testing using mixed approach. It is an explanatory sequential design research; quantitative data were measured in time, number of errors, Single Ease Question (SEQ) questionnaire score and System Usability Scale (SUS) score. They were used to evaluate the usability level of the application, and finger mapping data and participant comments were used to find more specific problems in the design or look for user patterns. Usability evaluation was carried out on 6 sub-applications from Go-jek and Grab companies. Good grouping of visual elements and the completion of a small task makes usability perceptions increase. Yet, the design problems that make usability perception decrease are touch targets that are too small in size, bad visual element grouping, too many items in one page, and unfamiliar operational gestures. This research has also found that high usability score is not always determined by visual elements. Navigation behavior has an important role in making good usability perception in users with visual impairment. A problematic visual design could be considered a problem in one navigation method, but not in another.